Tipología de consumo de alcohol en estudiantes de la carrera de Medicina Humana de la Universidad Nacional de Loja - Toala Saritama, Wagner Rogelio (2022)
Alcoholism is a disease characterized by excessive alcohol consumption, caused by multiple social, cultural and psychological causes, leading to the development of a variety of pathologies, in addition, alcohol consumers can be grouped according to the Jellinek typology. As alcohol consumption is a frequent problem in university students, this quantitative, descriptive, cross-sectional cohort study was developed with the aim of determining the type of alcohol consumption. 252 students participated in this study, of which 47.2 % (n=119) are in the range of 21 to 23 years old, 68.3% (n=172) are female, 77.8% (n=196) come from urban areas, the majority are single, 64.3% (n=162) live with their parents and 8.7% (n=22) live alone, 89.3% (n=225) only study and 10.7% (n=27) study and work. 66.27% (n=167) of students have consumed alcohol without presenting a Jellinek typology diagnosis, 15.48% (n=39) present an Alpha diagnosis, followed by Epsilon, Alpha + Epsilon, Delta, Gamma and Beta. It is important to point out that 9.92% (n=25) of students do not consume alcohol. A psychoeducational proposal was designed with the purpose of expanding knowledge about alcohol consumption, which it is proposed to socialize updated information on alcoholism, causes and effects on mental and physical health, propose measures to decrease alcohol consumption and identify body benefits when people stop drinking it.